2016
DOI: 10.1186/s12917-016-0940-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic detection of peste des petits ruminants virus under field conditions: a step forward towards disease eradication

Abstract: BackgroundThe devastating viral disease of small ruminants namely Peste des petits ruminants (PPR) declared as target for “Global Eradication” in 2015 by the Food and Agriculture Organization (FAO) and the World Organization for Animal Health (OIE). For a successful eradication campaign, molecular diagnostic tools are preferred for their specificity, efficacy and robustness to compliment prophylactic measures and surveillance methods. However, molecular tools have a few limitations including, costly equipment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In this way, LAMP detected as little as 11.3 ng/µl of RNA which is one serial dilution higher than detected by RT-PCR i-e, 10 -3 was the last dilution that could be detected; therefore, LAMP is 10-times more sensitive in comparison to RT-PCR. This finding is in-line with Ding et al (2014) and Ashraf et al (2017). These results showed that LAMP assay is useful for detection of PPRV at low levels especially for confirmation at early stages when virus titers are relatively low (Dadas et al, 2012;Balamurugan et al, 2014).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this way, LAMP detected as little as 11.3 ng/µl of RNA which is one serial dilution higher than detected by RT-PCR i-e, 10 -3 was the last dilution that could be detected; therefore, LAMP is 10-times more sensitive in comparison to RT-PCR. This finding is in-line with Ding et al (2014) and Ashraf et al (2017). These results showed that LAMP assay is useful for detection of PPRV at low levels especially for confirmation at early stages when virus titers are relatively low (Dadas et al, 2012;Balamurugan et al, 2014).…”
Section: Discussionsupporting
confidence: 63%
“…It is an efficient protocol which yields DNA in higher quantities that is enough for confirmation by visual examination. In case of RNA viruses, the RNA template is used directly as starting material for reverse transcription together with LAMP in a single step, hence making it suitable for diagnostic purpose (Wang et al, 2011;Ashraf et al, 2017). The process is based on strand displacement reaction and the target site is amplified via stem-loop structure rapidly with accuracy, selectivity and high specificity under the isothermal conditions (Parida et al, 2006;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report the development and evaluation of a rapid and simple one-step colorimetric reverse transcriptional loop-mediated isothermal amplification (RT-LAMP) assay, COVID-19-LAMP, for detection of SARS-CoV-2. RT-LAMP combines reverse transcriptase, DNA polymerase, pH indictor, and six primers to amplify RNA templates [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ], causing a drop in pH and, thus, a color change from pink to yellow. Since RT-LAMP involves both reverse transcription and DNA amplification at a constant temperature without the need for a PCR thermal cycler [ 25 ], it only requires simple equipment, namely benchtop centrifuges, heat blocks, and micropipettes.…”
Section: Introductionmentioning
confidence: 99%
“…A novel inexpensive RT-LAMP provides an isothermal method to amplify viral RNA without the requirement of expensive specific thermal cycler [29,30]. Moreover, RT-LAMP reagents can be stored at ambient temperature for at least 2 weeks.…”
Section: Reverse Transcription Loop-mediated Isothermal Amplificationmentioning
confidence: 99%